#TITLE_ALTERNATIVE# - PHYRUS HONGGORAHARDJO (NIM 15105069); Pembimbing : Dr. Ir. Irwan Meilano, M.Sc. dan Ir. Dina An, ARIS
Cimandiri Fault is an active fault in Southern Sukabumi, which runs in the direction from Pelabuhan Ratu, Sukabumi, Cianjur and Padalarang. Cimandiri Fault is formed because pushing force from subduction Australian oceanic plate to the bottom of Eurasian continent plate in the south of Java Island. Cimandiri Fault located in relatively high population area, if earthquake occur, it will cause loss and a lot of damage, so activity level of Cimandiri Fault is needed to be monitoring for anticipation and mitigation for incoming earthquake. For that purpose, GPS measurement is done using episodic static geodetic positioning (differential positioning) method four times, at 1-4 December 2006, 20-23 August 2007, 8-12 August 2008 and 21-14 July 2009. GPS survey is done using several dual frequency GPS receiver and the data is processed using Bernese Scientific Software ver. 5.0, and then calculating deformation vector, extensions parameter point and creating activity level model. Based on data processing result gives conclusion that Cimandiri Fault is Left-Lateral Strike-Slip Fault and Cimandiri Fault zone and surrounding move with the rates vary spatially between 1 to 20 mm/year, extension point is 0.1 to 4 microstrain and deformation accumulation level is 10 mm/year.